Experimental Investigation of Non-Verbal Communication in Eating Disorders. (March 2021) - Harrison, A.
Highlights: Difficulties in non-verbal communication may underlie the social disability reported by people with eating disorders (EDs) This was the first study to investigate non-verbal communication during a real-life social interaction in people with EDs compared to non-ED controls People with EDs make less use of hand gestures and show different body posture than controls during social interaction. There is no difference in facially-expressed emotions during social interaction between those with EDs and controls. People show less physiological arousal than controls during social interaction. Abstract: This study aimed to be the first to measure non-verbal communication in 25 eating disorder (ED) and 25 non-ED control participants during a naturalistic social interaction incorporating positive, negative and neutrally-valenced topics. The first hypothesis, that ED participants would show significantly reduced facial emotional expression than controls, was not supported. Supporting the second hypothesis of between-group differences in non-verbal behaviour, ED participants were less likely to lean in towards their interlocutor ( d =.81) discussing negatively-valanced topics and were more likely to be positioned upright when discussing positively-valenced topics ( d =.1.09) than controls. Irrespective of emotional valence, ED participants positioned their gaze on their interlocutor significantly less ( d =.29) and spent more time looking down ( d =.54), or away than controls ( d =.63). ED participants moved their hands along with speech significantly less ( d =.63) and gestured fewer real/hypothetical/imagined images/actions/objects) than controls ( d =.57), irrespective of emotional valence. Instead, ED participants indicated discomfort in the social interaction, touching their nose ( d =.89) or playing with their nails ( d =.95) more often than controls. ED participants, regardless of emotional valence, showed significantly lowered electro-dermal activity ( d =.60) than controls, supporting the exploratory hypothesis. People with EDs appear to make less efficient use of non-verbal communication than controls.